Organizing resistance and imagining alternatives in India - Varman, Rohit ca. 20./21. Jh; Vijay, Devi ca. 20./21. Jh (Cambridge University Press, 2022)
This volume examines the political economy of neoliberalism in India and offers cases of resistance and alternative organizing. It departs from existing conversations that focus on the state's policies and decisions, and focuses on the violence unleashed by corporate forces. It should be of interest to anyone curious about the collapse of crucial infrastructures such as healthcare and the news media, or the rhetoric of corporate social responsibility, and why there are people's movements and organizations rising from different geographies. While offering in-depth case studies of oraganisations within India, such as The Wire, The People's Archive of Rural India, Kudumbashree, and Left Word Books, it also informs conversations across the world on alternative forms of organizing. These accounts have two imperatives: first, to train our attention on corporations and where capitalism produces its vast waste lands. Second, to imagine the possibilities of another world. The contributors to this volume write to resist the status quo, explore alternative ways of organizing, re-imagine social relations, and rekindle hope